Ultrasound-guided foam sclerotherapy for chronic venous disease with ulcer. A prospective multiple outcome cohort study - Abreu,Guilherme Camargo Gonçalves de (2020)
Abstract Background Chronic Venous Disease (CVD) is the main cause of chronic leg ulcers. Varicose veins are the most frequent cause of venous leg ulcers (VLU). 50.9% of Brazilian women have varicose veins and ulcer prevalence is as high as 4%. Ultrasound-guided foam sclerotherapy (UGFS) is a low-cost treatment option for varicose veins. Objectives To analyze UGFS outcomes in patients with VLU. Methods Prospective consecutive single center cohort study. Patients with great saphenous vein (GSV) reflux and VLU were treated and followed-up for 180 days. The following were studied: quality of life (QoL), disease severity, healing, and elimination of GSV reflux. The Aberdeen questionnaire, a venous clinical severity score, and Duplex scanning (DS) results were analyzed. Results 22 patients aged 35 to 70 years were treated. There was improvement in quality of life, disease severity reduced, and ulcer diameter reduced (p < 0.001; ANOVA). 77.27% of VLU healed completely (95%CI: 59.76-94.78%). The dimensions of 20/22 VLU reduced (90.91%; 95%CI: 78.9-100%). GSV reflux was eliminated in 63.64% (95%CI: 43.54-83.74%). Men had greater QoL benefit and women had more complications. There were no severe complications. The VLU that had healed completely at the end of the study were smaller at baseline than those that did not completely heal. The GSV that were completely occluded at the end of the study were smaller at baseline than those that were not completely occluded (p < 0.05; Mann-Whitney). Conclusion The results suggest that most patients benefited from UGFS.